4. CARDIORESPIRATORY RESPONSE DURING THE 1-MIN SIT TO STAND TEST IN CHRONIC OBSTRUCTIVE PULMONARY DISEASE (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the changes in cardiovascular and respiratory indices during the 1-minute sit-to-stand test in patients with chronic obstructive pulmonary disease.Subjects and methods: Cross-sectional study of 122 patients with stable chronic obstructive pulmonary disease. Each participant performed two 1-minute sit-to-stand test tests 30 minutes to 1 hour apart. The measurements recorded during the second test were included in the data analysis. Peripheral oxygen saturation (SpO2) and heart rate were measured using a finger pulse oximeter and the difference between the baseline (before the start of the test) and the final (at the end of the test) values was calculated. Exercise-induced desaturation was considered whenever a decrease in SpO2 of ≥ 4% occurred. Dyspnea was assessed immediately after each test using a modified Borg scale.Results: After the test, the mean heart rate change was 14.3 ± 3.6 beats, with severe patients having a slightly greater heart rate change than mild patients (difference 1.7 ± 0.7; p = 0.01). Oxygen saturation decreased significantly in the severe group and to a greater extent than in the mild group, p < 0.001.Conclusions: The 1-minute sit-to-stand test causes less hemodynamic stress for patients with chronic obstructive pulmonary disease.
Keywords: 1-minute sit-to-stand test, chronic obstructive pulmonary disease, cardiorespiratory indices.